The influence of leadership style on performance with motivation as mediation (study on employees of Metro City Trade Services during pandemi) - Putra, Muhammad Fadly; Ahadiyat, Ayi; Keumalahayati, Keumalahayati (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: This study aims to analyze the mediating role of motivation in the influence of leadership style on employee performance at the Metro City Trade Office during the pandemic period. Research Methodology: The research applied a quantitative survey approach with census sampling involving 300 employees. Data were collected through online questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), including tests of validity, reliability, and hypothesis testing. Results: The findings indicate that leadership style does not have a direct and significant effect on employee performance. However, leadership significantly influences motivation, and motivation in turn positively and significantly affects performance. Furthermore, motivation is proven to mediate the relationship between leadership and performance, highlighting its strategic role in improving organizational outcomes. Conclusions: Motivation is a crucial factor in enhancing employee performance under pandemic-related work conditions. Leadership’s impact becomes effective only when it strengthens employee motivation, indicating that motivational support is essential for sustaining performance in dynamic and uncertain contexts. Limitations: The study is limited to one public sector organization and focused solely on leadership, motivation, and performance variables. The research also coincided with a leadership transition, which may have influenced employee responses. The use of PLS-SEM also restricts broader generalization. Contribution: This research contributes to human resource management practices in the public sector by showing the importance of motivation as a mediating factor. It offers practical insights for leaders to strengthen motivation in order to enhance employee performance, particularly in dynamic work settings.